Reliability, Validity, and Feasibility of the Mayo Gastro-Eso-phag¬eal Reflux Questionnaire (GERQ) in a Persian-Speaking Population" - S Nasseri-Moghaddam; H Razjouyan; R Habibi; K Rafaat-Zand; B Ahrari; M Nouraie; R Majdzadeh; H Vahedi; R Malekzadeh (Tehran University of Medical Sciences, 2008)
Background: Gastroesophageal reflux disease (GERD) is prevalent in the West. Mayo-GERQ is one of the most widely used questionnaires for screening GERD. We validated GERQ in an Iranian population. Methods: The Mayo-GERQ was translated into Persian (P-GERQ) and reviewed and commented by two gastroenterologists. Eleven lay-people filled it in and commented on it. Reliability was assessed by test-retest within 2-6 wks in 53 hospital staff. Concurrent-validity was checked in another 53, comparing the results of the self-administered questionnaire with the questionnaires filled in by a gastroenterologist interviewing them. Weighted-kappa (kw) statistics was used. Time needed to complete the questionnaire, practicability of the directions and linguistic eloquence were checked (feasibility indices). Results were used to modify P-GERQ. The modified P-GERQ was tested in another 99 hospital employees in the same manner. Results: Phase-one; One-hundred seventeen subjects were enrolled (46 men). Mean time for completion was 23.7 minutes. Mean kw for reliability was 0.47 and that for validity 0.26. Sources of poor performance were sought, P-GERQ was revised and underwent validation again (2nd phase). Phase-two: Ninety-nine individuals were enrolled (37 men). The modified P-GERQ took 15.8+/-11.9 min to complete. k-values for concurrent-validity of major symptoms (acid-regurgitation, heartburn) were 0.70 and 0.67 respectively. Corresponding k-values for reliability were 0.57 and 0.80. Conclusions: P-GERQ was not valid initially. After making appropriate technical and linguistic changes, it achieved acceptable validity, reliability and feasibility. In addition to making available a useful tool for population-based studies, our results underscore the importance of validation before adopting a translated questionnaire.